Studies on ceiling laws : case studies from Bihar - Ashokvardhan, C. (Mussoorie, 2004)
The present volume is a compilation of the gist of some judgements delivere by the author during his stint in the Board of Revenue, Bihar.
Keywords: Ceiling law; IAS as an author